2016
DOI: 10.1016/j.physa.2015.12.147
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguration dynamics in folded and intrinsically disordered protein with internal friction: Effect of solvent quality and denaturant

Abstract: We consider a phantom chain model of polymer with internal friction in a harmonic confinement and extend it to take care of effects of solvent quality following a mean field approach where an exponent ν is introduced. The model termed as "Sol-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 72 publications
(125 reference statements)
0
11
0
Order By: Relevance
“…50 Indeed the effect of internal friction on the rheology and dynamics of polymers has been studied with bead-spring-chain models, in which a dashpot with a common value of the damping coefficient is included in parallel with each of the connecting springs. 32,51,52 It would be interesting to explore the connection between the internal friction coefficient estimated from the average dissipated work (in the limit of zero solvent viscosity) from such a model, and the damping coefficient of each dashpot in the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Indeed the effect of internal friction on the rheology and dynamics of polymers has been studied with bead-spring-chain models, in which a dashpot with a common value of the damping coefficient is included in parallel with each of the connecting springs. 32,51,52 It would be interesting to explore the connection between the internal friction coefficient estimated from the average dissipated work (in the limit of zero solvent viscosity) from such a model, and the damping coefficient of each dashpot in the model.…”
Section: Discussionmentioning
confidence: 99%
“…1 (a)), subjected to fluctuating random forces from the bath of solvent molecules it is immersed in. This model has been widely invoked in rheological, 1,[29][30][31] as well as biophysical contexts, 6,12,32 to capture the effects of internal friction in polymers. Within this model, the spring accounts for the entropic elasticity in the polymer molecule, whereas the dissipative effect from the myriad sources of internal friction is captured by the dashpot.…”
Section: Introductionmentioning
confidence: 99%
“…66) and as an analytical expression for asymptotic values of the ratio at high shear rates (see Eq. (17) in Ref. 66).…”
Section: Comparison Of a Model With Large IV Parameter With A Rigimentioning
confidence: 94%
“…[1][2][3][4] The inclusion of a resistive force proportional to the rate of change of the connector vector between beads in addition to the spring force has been shown to lead to a finite limiting value for the infinite frequency limit of the dynamic viscosity, 3 instantaneous stress jumps at the inception of steady shear flow, 5 and to a shear-rate dependent viscosity. 6,7 More recently, several experimental, [8][9][10][11][12] theoretical [13][14][15][16][17][18][19] and simulation studies [20][21][22][23] have shown that the presence of internal friction modulates conformational changes in a number of different biological contexts. This includes slowing down the process of protein folding, 8 affecting the dynamics of intermolecular interactions in intrinsically disordered proteins, 10,11 and influencing stretching transitions in single biomolecule force spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…For dry internal friction, a spring-dashpot model [1,3,44,45] is considered where the molecule is represented as massless beads connected by a spring and dashpot in parallel with each other. The spring accounts for entropic elasticity, while dissipative effects due to internal friction are captured by the dashpot [46].…”
Section: Introductionmentioning
confidence: 99%